Isis Pelagia : images, names and cults of a goddess of the seas - Bricault, Laurent, (Religions in the Graeco-Roman World;, 2020)
In Isis Pelagia: Images, Names and Cults of a Goddess of the Seas<>/i>, Laurent Bricault, one of the principal scholars of the cults of Isis, presents a new interpretation of the multiple sources that present Isis as a goddess of the seas. Bricault discusses a wealth of relatively unknown archaeological and textual data, drawing on a profound knowledge of their historical context. After decades of scholarly study, Bricault offers an important contribution and a new phase in the debate on understanding the "diffusion" as well as the "reception" of the cults of Isis in the Graeco-Roman world. This book, the first English-language monograph by the leading French scholar in the field, underlines the importance of Isis Studies for broader debates in the study of ancient religion.